Immune response by nasal delivery of hepatitis B surface antigen and codelivery of a CpG ODN in alginate coated chitosan nanoparticles - Borges, Olga (2008)
Alginate coated chitosan nanoparticles were previously developed with the aim of protecting the antigen, adsorbed on the surface of those chitosan nanoparticles, from enzymatic degradation at mucosal surfaces. In this work, this new delivery system was loaded with the recombinant hepatitis B surface antigen (HBsAg) and applied to mice by the intranasal route. Adjuvant effect of the delivery system was studied by measuring anti-HBsAg IgG in serum, anti-HBsAg sIgA in faeces extracts or nasal and vaginal secretions and interferon-[gamma] production in supernatants of the spleen cells. The mice were primed with 10 [mu]g of the vaccine associated or not with nanoparticles and associated or not with 10 [mu]g CpG oligodeoxynucleotide (ODN) followed by two sequential boosts at three week intervals. The association of HBsAg with the alginate coated chitosan nanoparticles, administered intranasally to the mice, gave rise to the humoral mucosal immune response. Humoral systemic immune response was not induced by the HBsAg loaded nanoparticles alone. The generation of Th1-biased antigen-specific systemic antibodies, however, was observed when HBsAg loaded nanoparticles were applied together with a second adjuvant, the immunopotentiator, CpG ODN. Moreover, all intranasally vaccinated groups showed higher interferon-[gamma] production when compared to naïve mice.